SYNTACTIC AND SEMANTIC INTERACTION IN THE DESCRIPTION OF THE ENGLISH GERUND-PARTICIPLE WITH PHYSICAL PERCEPTION VERBS - Gomez Castejon, Maria Angeles (International Journal of English Studies, 2009)
English physical perception verbs can appear followed by an NP (Noun Phrase) and an –ing form. In the literature, they are generally assumed to represent two separate constituents. However, we claim that an alternative interpretation is also possible: the “NP + -ing form” can be considered as a single constituent. We provide semantic, syntactic and thematic evidence in favour of this hypothesis. We will especially dwell on the relationship between physical and cognitive perception verbs. Finally, we will discuss the implications of this analysis on the possible readings of the –ing form with physical perception verbs (abstract and concrete readings).